Urban Land Markets in Durres - Golgota, Alma; PhD Cand. ark. Boriana Vrusho (European Journal of Multidisciplinary Studies, 2016)
After the fall of communist regime, Durres passed through an uncontrolled urban development and painful migration and emigration. Albania passed into process of transition from a centrally planned economy to a free-market based economy. Radical political, economic and social reforms had been undertaken. This means basic political and market institutions as well as the administrative, regulatory and policy frameworks required for a market economy had been developed. During the 1990’s Albania went through a transformation of its entire economy that changed civil society, ownership structures and the labor market. As in other cases happen in transition, Durres experienced many problems with self-employment in the informal sector and small commerce and industries. The lack of formal job opportunities stimulated emigration of the working active population to neighboring countries, such as Greece and Italy. This explains the volume of remittances that are regularly sent into the country. Also thousands of farmers have chosen to abandon their villages and settlements and seek opportunities in the city of Durres. The city became the focus of mass emigrations from Albania. Many people migrated to Italy and other countries. Very large rates of growth among the 1990’s, were result of increased movement of population to urban areas, which continued in high rates until 2003. The annual growth rate was 7 percent, but after 2003 it decreased in 1.4 percent per year. Unemployment remains a big issue for the city of Durres, despite the progress that has taken place. The official rate of unemployment is 11 percent, but due to many unemployed persons who do not register as such, the unemployment rate is much higher (around 25 percent). Data from Standard Measurement Survey Living (VMNJ) in 2002 show that poverty rate is about 25 percent.